PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA BELAJAR AGAMA ISLAM PADA MAJELIS PENGAJIAN ZAWIYAH NURUN NABI GAMPONG LAMBHUK KOTA BANDA ACEH - Nelsa Listia Amanda; Amiruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The use of social media in Islamic religious learning offers significant opportunities; however, it has not been fully optimized in Majelis Pengajian Zawiyah Nurun Nabi, Gampong Lambhuk, Banda Aceh. The main problems include the tendency of congregants, especially women, to use social media more for personal purposes, low digital literacy, and limited interaction and understanding of digital learning materials. This study aims to analyze the use of social media as a learning tool, the forms of digital learning activities, its impact on understanding and participation, and the challenges faced. This research employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation involving 21 respondents. Data analysis was conducted through data reduction, data display, and conclusion drawing with triangulation. The results show that social media utilization falls into good to very good categories, with scores ranging from 47 to 92 across indicators. Social media improves access, understanding, and religious practice, although its use remains uneven due to literacy and engagement issues.